Exploring Narrative Accounts of Indonesian Academic Returnee: Expectation vs Reality - Trias Novita Imawati; Irfan Rifai (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
Academic returnees have become a trending issue recently. One issue concerns the reported challenges when they returned to their home country and re-integrated into their academic environment. This research aims to better understand the Indonesian academic returnee returning to the Indonesian academic sphere, particularly the returnee who teaches English in higher education. This study is grounded under narrative inquiry. Narrative interviews with four English lecturers, three women, and a man, were used to unpack their challenging experiences. The present research shows two types of challenges faced by Indonesian academic returnees, academic and social culture. Concerning academic culture, the returnee often experienced different conceptions of the current English language teaching methods. Social culture is closely related to their inconvenience of being on-time and disciplined persons. This research is expected to provide more nuanced about the challenges of academic returnees re-integrating into the academic milieu. Keywords: narrative accounts, Indonesian academic returnee, reverse culture shock